Breaking and making of rings: a method for the preparation of 4-quinolone-3-carboxylic acid amides and the expensive drug ivacaftor - Vasudevan, N.; Jachak, Gorakhnath R.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2015)
A simple and convenient method to access 4-quinolone-3-carboxylic acid amides from indole-3-acetic acid amides through one-pot oxidative cleavage of the indole ring followed by condensation (Witkop-Winterfeldt type oxidation) was explored. The scope of the method was confirmed with more than 20 examples and was successfully applied to the synthesis of the drug Ivacaftor, the most expensive drug on the market.
Keywords: Amides; Drug design; Fused-ring systems; Oxidation; Ozonolysis

Synthesis and biological evaluation of hoshionolactam-based compounds - Jachak, Gorakhnath R.; Elizebath, Drishya; Shukla, Anurag; Shanmugam, Dhanasekaran; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2021)
In search of novel antitrypanosomal agents based on hoshinolactam (IC50=3.9 nM), we disclose the synthesis and biological evaluations of 14 different analogues of the natural product using combinations of different acids and lactams. Antitrypanosomal activity assays revealed that the synthesized analogues were less potent than the parent natural product.
Keywords: Hoshinolactam; Ozonolysis; Parasitic diseases; Trypanosoma